(untitled) (Proceedings of International Conference on Special Education, 2015)
Life skill is needed by each individual being for surviving and it is not an exception for children with special needs. Life skill can be developed through sustainable learning process. On inclusive school, there is individual learning program for children with special needs which includes; 1) general life skill (GLS) with personal skill and social skill as its scope. 2) Specific life skill (SLS) with academic skill and vocational skill as its scope. Children with mild intellectual disabilities have below average academic skill but they can be given vocational skill which is suitable with their capability. On the high school level, the learning process focused on the students’ independency. This independency can be reached if the students have self-actualization skill and functional academic skill such as counting money, shopping, and reading items’ label. This study will discuss vocational skill learning for children with mild intellectual disabilities on one of the inclusive high school in Bandung City.